ANALISIS KINERJA BIROKRASI DALAM MENINGKATKAN PELAYANAN PUBLIK PADA DINAS PENDIDIKAN KABUPATEN SUMENEP - Effendy, Sachlan (POLICY CORNER, 2014)
This study was directed to evaluate and explain the phenomenon of the performance of the government bureaucracy at the Department of Education case Sumenep using a process approach (internal process approach), especially to understand and explain the phenomenon in terms of efficiency of service, work, teamwork, leadership and relationship with subordinates. This research was conducted at the Department of Education Sumenep using descriptive approach, the sample is Sumenep Service employee. While the analysis of research data using the technique of editing, coding, data tabulation, and statistical approaches to describe the data. Based on these results Performance Level Sumenep Education Office in carrying out the functions are in a moderate level of performance, efficiency organizations Sumenep Education Department in achieving educational management functions are in a good level.Â Keyword: Performance, bureaucracy, the Department of Education